Teachers' Beliefs and Practices Regarding the Genre-Based Approach to English Learning in Junior High School - Shafira Zulmeida; Basikin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to investigate English teachers' beliefs and practices regarding the Genre-Based Approach in the classroom, as well as the effectiveness of its implementation in improving students' language understanding and skills. A case study was conducted in three junior high schools, including one private school, with data collected through interviews, classroom observations, and teaching module analysis. The results show that most teachers had a limited understanding of GBA, with only one teacher demonstrating deeper knowledge. Teachers' beliefs about GBA were influenced by three factors: the importance of GBA, its impact on students, and the sources of their beliefs. This study highlights the importance of professional development and curriculum support to enhance the implementation of GBA in English language teaching.